(untitled) (Third Sector Social Economic Review, 2019)
According to Efficient Market Hypothesis, all information is instantly reflected in prices. Simultaneous reflection of information on prices removes the possibility of investors getting return more than expected from these markets. However, Investors have always shown that they are not acting rationally and that they sometimes give similar responses to similar situations. In Behavioral Finance, investors tend to be influenced by many sociological, psychological and environmental influences. Especially in recent years, the existence of terrorist attacks, which started to damage the sociological, psychological and administrative structures of societies and start to harm economically, constitute which is the main starting point of our work. In this perspective, the main purpose of this research is to figure out the potencial effects of 94 terrorist attacks that occured in Turkey between the dates 20.09.2011-17.02.2017, on Borsa İstanbul 100 Index. To reveal the impacts, terrorist attacks examined in two subcategories to get in detain on the effects of the terrorist attacks take place on holidays or weekday days to observe more clearly the response given by the market. As a result of the analysis, it is not possible to advocate the existence of a negative or positive trend in the market clearly in the context of the data set and method used. Nevertheless, statistically significant results obtained demonstrates that the BIS 100 Index is not efficient in a semi-strong form within the scope of the research.